2014
DOI: 10.1080/13546805.2014.922062
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self-report and performance-based measures of everyday functioning in individuals with schizophrenia: implications for measure selection

Abstract: The pattern of interrelationships among these self-report and performance-based measures suggests that they tap different aspects of everyday functioning. This has important implications for measure selection, particularly for evaluating intervention outcomes. When targeting symptoms, a self-report measure like the ILSS-SR may be more appropriate, whereas a performance-based measure may be more sensitive to functional changes subsequent to treatments targeting cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The The UPSA is a performance-based measure that has reliably demonstrated the ability to predict real-world functioning in schizophrenia [101]; it has high correlations with measures of personal care skills, interpersonal skills, and community activities [101,102], and has demonstrated high sensitivity to functional changes [103]. The SCoRS is a clinicianadministered interview, to both participants and informants, which assesses cognition-related daily functioning.…”
Section: Daily Functioningmentioning
confidence: 99%
“…The The UPSA is a performance-based measure that has reliably demonstrated the ability to predict real-world functioning in schizophrenia [101]; it has high correlations with measures of personal care skills, interpersonal skills, and community activities [101,102], and has demonstrated high sensitivity to functional changes [103]. The SCoRS is a clinicianadministered interview, to both participants and informants, which assesses cognition-related daily functioning.…”
Section: Daily Functioningmentioning
confidence: 99%
“…Finally, the use of a self-report scale of living skills was potentially problematic given that completion is reliant on functional memory and introspection. Capacity-based functional measures (e.g., UCSD Performance-Based Skills Assessment), which are more strongly correlated with cognition, may be more sensitive to potential far-transfer (Elliott & Fiszdon, 2014;Harvey, Velligan, & Bellack, 2007). In retrospect, the ILSS-SR may have been more suitable in an intervention targeting psychiatric symptoms given recently reported relationships between the ILSS-SR and emotional distress (Elliott & Fiszdon, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…Only one study assessed the correlation between the two scales [83], reporting a value of 0.47. The full UPSA and the Independent Living Skills Survey (ILSS) were jointly evaluated in two studies [46, 47]. One study reported a correlation between the two scales of 0.13 ( p =0.24) and concluded that the UPSA did not correlate well with the ILSS [46].…”
Section: Resultsmentioning
confidence: 99%
“…The full UPSA and the Independent Living Skills Survey (ILSS) were jointly evaluated in two studies [46, 47]. One study reported a correlation between the two scales of 0.13 ( p =0.24) and concluded that the UPSA did not correlate well with the ILSS [46]. The other study reported a correlation of 0.16 ( p =0.28) [47].…”
Section: Resultsmentioning
confidence: 99%